2021
DOI: 10.1016/j.apsusc.2021.149148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mn addition on catalytic performance of Cu/SiBEA materials in total oxidation of aromatic volatile organic compounds

Abstract: Dealuminated BEA zeolite (SiBEA) was chosen as a support of metal oxide(s) phase for catalytic combustion of volatile organic compounds (VOCs). Copper and/or manganese oxide(s) were deposited at various Cu/Mn molar ratios. Factors influencing the catalytic activity were found by chosen physicochemical methods, including XRD, XRF, lowtemperature N 2 adsorption, FT-IR, UV-Vis-DRS, STEM-EDX, XPS and H 2 -TPR. Depending on the chemical composition, CuO, (Cu x Mn 3-x ) 1-δ O 4 , Cu-doped Mn 3 O 4 or Mn 2 O 3 was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…However, it is worth noting that, compared to the catalyst supported by H‐Beta (i. e., CoO x /H‐Beta), the CoO x /deAl‐Beta catalyst showed very similar conversion of toluene and yield of CO 2 and CO. Similarly, highly dispersed bimetallic CuMnO x phases were supported on deAl‐Beta as well by varying the Cu/Mn ratio during impregnation [27] . The mixed oxides catalysts with increased surface oxygen vacancies showed a better catalytic performance than the monometallic catalysts (i. e., Cu/deAl‐Beta and Mn/deAl‐Beta).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, it is worth noting that, compared to the catalyst supported by H‐Beta (i. e., CoO x /H‐Beta), the CoO x /deAl‐Beta catalyst showed very similar conversion of toluene and yield of CO 2 and CO. Similarly, highly dispersed bimetallic CuMnO x phases were supported on deAl‐Beta as well by varying the Cu/Mn ratio during impregnation [27] . The mixed oxides catalysts with increased surface oxygen vacancies showed a better catalytic performance than the monometallic catalysts (i. e., Cu/deAl‐Beta and Mn/deAl‐Beta).…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies also demonstrated the successful development of supported metal catalysts on deAl‐Beta for catalytic oxidation of toluene including monometallic CoO x /deAl‐Beta [26] and bimetallic CuMnO x /deAl‐Beta, [27] in which a homogeneous distribution of the active phases over the support was achieved. For example, highly dispersed isolated mononuclear Co(II) species, small Co(II) oxide clusters and/or Co 3 O 4 crystallites were incorporated into the framework of Beta zeolite by changing the amount of the introduced Co from 3 to 9 wt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,8] As catalysts are the most critical element of catalytic oxidation, it is extremely important to provide an affordable, effective, and simple catalyst for the elimination of VOCs. [9,10] Metal oxides have become one of the most important materials in catalytic oxidation processes due to their stability and potent oxidation capacity, such as Mn, [11] Co, [12] Cu, [13] and Fe. [14] As compared with other transition metal oxides, manganese-based oxides have superior catalytic performance in the catalytic oxidation of VOCs due to their adaptable crystal type, valence, and morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxides have become one of the most important materials in catalytic oxidation processes due to their stability and potent oxidation capacity, such as Mn, [ 11 ] Co, [ 12 ] Cu, [ 13 ] and Fe. [ 14 ] As compared with other transition metal oxides, manganese‐based oxides have superior catalytic performance in the catalytic oxidation of VOCs due to their adaptable crystal type, valence, and morphology.…”
Section: Introductionmentioning
confidence: 99%